2021
DOI: 10.7554/elife.61951
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein plasma membrane localization correlates with cellular phosphatidylinositol polyphosphate levels

Abstract: The Parkinson's disease protein α-synuclein (aSyn) promotes membrane fusion and fission by interacting with various negatively charged phospholipids. Despite postulated roles in endocytosis and exocytosis, plasma membrane (PM) interactions of αSyn are poorly understood. Here, we show that phosphatidylinositol 4,5-bisphosphate (PIP2) and phosphatidylinositol 3,4,5-trisphosphate (PIP3), two highly acidic components of inner PM leaflets, mediate plasma membrane localization of endogenous pools of αSyn in A2780, H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 81 publications
(117 reference statements)
3
28
0
Order By: Relevance
“…While the pathological relevance of αS is generally established, its function remains elusive, although growing evidence points to a role in synaptic vesicles (SVs) trafficking ( Auluck et al, 2010 ; Burre, 2015 ). A recursive feature in most of the putative functions of αS involves binding to biological membranes ( Lorenzen et al, 2014 ; Snead and Eliezer, 2014 ; Fusco et al, 2018 ; Jacob et al, 2021 ), an interaction relevant to the normal form of αS in vivo ( Newberry et al, 2020a ; Newberry et al, 2020b ) and influencing its aggregation ( Perrin et al, 2001 ; Zhu and Fink, 2003 ; Breydo et al, 2012 ; Comellas et al, 2012 ; Galvagnion et al, 2015 ; Antonschmidt et al, 2021 ) and the toxicity of its oligomeric aggregates ( Fusco et al, 2017 ). This interaction has been observed in different biological contexts, including the regulation of the homeostasis of SVs during neurotransmitter release ( Wislet-Gendebien et al, 2006 ; Auluck et al, 2010 ), the localization to mitochondrial membranes or mitochondrial-associated membranes ( Maltsev et al, 2013 ; Plotegher et al, 2014 ; Menges et al, 2017 ; Ordonez et al, 2018 ; Ramezani et al, 2019 ), where it has been proposed to mitigate the effects of oxidative stress, or the binding to lysosomal membranes ( Bourdenx et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the pathological relevance of αS is generally established, its function remains elusive, although growing evidence points to a role in synaptic vesicles (SVs) trafficking ( Auluck et al, 2010 ; Burre, 2015 ). A recursive feature in most of the putative functions of αS involves binding to biological membranes ( Lorenzen et al, 2014 ; Snead and Eliezer, 2014 ; Fusco et al, 2018 ; Jacob et al, 2021 ), an interaction relevant to the normal form of αS in vivo ( Newberry et al, 2020a ; Newberry et al, 2020b ) and influencing its aggregation ( Perrin et al, 2001 ; Zhu and Fink, 2003 ; Breydo et al, 2012 ; Comellas et al, 2012 ; Galvagnion et al, 2015 ; Antonschmidt et al, 2021 ) and the toxicity of its oligomeric aggregates ( Fusco et al, 2017 ). This interaction has been observed in different biological contexts, including the regulation of the homeostasis of SVs during neurotransmitter release ( Wislet-Gendebien et al, 2006 ; Auluck et al, 2010 ), the localization to mitochondrial membranes or mitochondrial-associated membranes ( Maltsev et al, 2013 ; Plotegher et al, 2014 ; Menges et al, 2017 ; Ordonez et al, 2018 ; Ramezani et al, 2019 ), where it has been proposed to mitigate the effects of oxidative stress, or the binding to lysosomal membranes ( Bourdenx et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Many studies have demonstrated that α-Syn fibrils spread from neuronal networks, and once internalized into neuronal cells in proximity, fibrils misfold the endogenous α-Syn in acceptor cells. 8 The extracellular α-Syn fibrils affect microglia and astrocytes causing degeneration of dopaminergic neurons. α-Syn internalization is also seen in many cell types, such as neurons, F I G U R E 1 Legend on next page.…”
Section: Introductionmentioning
confidence: 99%
“…Once a substance get internalized, it is membrane trafficked to various cellular compartments forming early and late endosomes, followed by either degradation in lysosome or recycling back to the plasma membrane 6,7 . Many studies have demonstrated that α‐Syn fibrils spread from neuronal networks, and once internalized into neuronal cells in proximity, fibrils misfold the endogenous α‐Syn in acceptor cells 8 . The extracellular α‐Syn fibrils affect microglia and astrocytes causing degeneration of dopaminergic neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The regions which retain a high probability of forming an α-helical structure in the AT simulations match well with the regions of higher α-helical propensity observed in the NMR measurements. The small differences in the profiles may reflect the different lipids employed (POPG vs DHPC/DMPG/PIP 2 ; interestingly a recent study has suggested αS may interact with PIP 2 in cell membranes) and also the differences between a lipid bilayer and a bicelle environment, although in both the simulations and the experiments, the membrane surface was predominantly anionic. Overall, these profiles, both experimental and computational, agree well with the suggestion from earlier NMR studies of a tightly bound N-terminal helix and a more transiently interacting subsequent helical region and align well with a recent model of αS interactions with lipid-bilayer nanodiscs …”
Section: Resultsmentioning
confidence: 98%
“…Exogenously delivered αS appears to be present largely as a disordered monomer in the cytoplasm of mammalian cells . More recently, the anionic lipid phosphatidylinositol phosphate (PIP 2 ) has been implicated in localizing αS to the plasma membrane . Disease-causing mutations alter lipid-induced generation of fibrils .…”
Section: Introductionmentioning
confidence: 99%